Client resistance to hepatitis C treatment initiation in opioid agonist treatment clinics in Sydney, Australia: A qualitative study. (28th November 2021) - Coupland, Heidi; Day, Carolyn; Haber, Paul; Pritchard‐Jones, Janice; McKee, Kristen; George, Jacob; McCaughan, Geoff
Abstract: Introduction: Opioid agonist treatment (OAT) clinics play a key role in achieving elimination of hepatitis C virus (HCV) globally. Previous research has identified barriers to HCV treatment uptake in OAT clinics; however, most studies were conducted prior to the introduction of direct‐acting antiviral treatments (DAA). It remains unclear whether progress has been made in responding to barriers and what challenges persist in this setting. Methods: Semi‐structured in‐depth interviews were conducted with staff ( n = 20) and clients ( n = 15) in two OAT clinics in Sydney, Australia. Interviews were transcribed verbatim and analysed using constant comparative methods. Results: Despite progress in integrating hepatitis C care in the clinics, competing priorities, concerns about side‐effects, distrust of staff, health problems and difficulties accessing testing and medication persisted as key reasons why clients had not initiated treatment. Most clients preferred to postpone treatment and focus on other priorities and some highlighted lack of medical evidence for urgent treatment. Pressure on services to achieve elimination targets within set time frames was a primary driver of repeated offers of treatment by staff and the framing of clients' preferences for postponing treatment, as a barrier. Discussion and Conclusion: Current timelines for HCV elimination targets may have galvanised services into action but may have also created tensions at the coalface due to disparities between staff and clients' priorities. The involvement of peer workers and mechanisms to ensure continued follow up with clients about DAA treatments is required. Public health timelines for HCV elimination need to be informed by affected communities' priorities.